Confession and estimation of account receivable (Journal of Economic Research & Business Administration, 2016)
Effective control system is needed an account receivable for strength ening of the financial state of organization, that, in turn, must assist the height of volume of sales, profit and increase of competitiveness. Realiza tion of these tasks is possible only at presence of to the complete, reliable estimation and timely confession in the financial reporting of account re ceivable. In the article the order of confession of account receivable, order of estimation of net cost of accounts receivables and reflection of them, is examined on the accounts of record-keeping. Similarly in the article con sidered order of reflection on the accounts of record-keeping of discount from a price and from sales, return of the sold commodities and order of processing of primary documents.
Keywords: account receivable; confession; estimation; discount from a price and sale; return of the sold commodities; overvalue etc.